Phase Change Materials Applications to Optimize Cooling Performance of Buildings in the Mediterranean Area: A Parametric Analysis. (November 2015) - Guarino, Francesco; Longo, Sonia; Cellura, Maurizio; Mistretta, Marina; La Rocca, Vincenzo
Abstract: Building integrated thermal energy storage systems cover a wide range of techniques and solutions depending on technology applications and aims. They however all have in common the concept behind: being able to store energy for later use in order to reduce the time mismatch between energy availability and demand. In this context, Phase Change Materials (PCMs) fit the above description, since they would allow for mostly isothermal phase change within normal thermal comfort range. In order to face the typical challenges of the Mediterranean climate, the following concept was elaborated: the idea is to use the phase change mechanics as a substitute to the thermal inertia of massive walls to obtain a similar effect in lightweight structures. A simulated test room was arranged and through parametric analysis the potential of PCM for energy efficiency in connection to natural ventilation strategies was assessed. Simulation results vary according to the configuration analysed but in all cases, cooling consumption reduction reached at least 40% with the use of PCMs. Air Temperature during peak hours in summer can be reduced by more than 7-8 °C.